Characterization, agricultural aptitude and use capacity of ‘Argissolo Vermelho-Amarelo Eutrófico abrúptico: a case study in Itapetinga -BA - Oliveira, Raul Silva; Moreau, Ana Maria Souza dos Santos; Reis, Amanda Dias dos; Tomaz, Aline Roma (Revista de Ciências Agroveterinárias, 2023)
The livestock agriculture from Itapetinga are in area of Argissolos. The management of livestock has caused compaction. Thus, the purpose of the study was: i) describe the morphological, Chemical, and physical of the Argissolo Vermelho-Amarelo; ii) classify your agricultural aptitude and use capacity. The morphological characterization was described: depth, color, structure, texture, consistency, and transition. The physical analysis was: texture and clay dispersed in water. The Chemical analysis determined the cations (Ca2+, Mg2+ Na+, K+, Al3+ e H+), pH, carbon, nitrogen and phosphorus. The oxides Al2O3 and Fe2O3were determined. The “Sistema de Avaliação de Aptidão Agrícola das Terras” and “Sistema de Capacidade de Uso” were used for classification. The soil was classified with Argissolo Vermelho-Amarelo Eutrófico abrúptico. Your aptitude has been graded as 1abC and IV E-3 to use capacity. Therefore, the use of soil is incorrect, because the perennial pasture with practices against erosion is the correct form of use. The abrupt character with compaction by the animals result in losses of the productive capacity of the soil. This is reality of the microregion of Itapetinga because most of the territory is in area of Argissolos Vermelho-Amarelos Eutróficos, totaling 41% of the total area.